Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1093/infdis/jir385
|View full text |Cite
|
Sign up to set email alerts
|

A376S in the Connection Subdomain of HIV-1 Reverse Transcriptase Confers Increased Risk of Virological Failure to Nevirapine Therapy

Abstract: The A376S substitution in the connection subdomain of HIV-1 RT causes selective nevirapine resistance and confers an increased risk of virological failure to nevirapine-based ART.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 40 publications
0
16
0
Order By: Relevance
“…34 The N348I mutation occurred in 11% of viruses in Southern Brazil and it is associated with major resistance to nevirapine, etravirine, and rilpivirine, and as an accessory mutation for thymidine analogs. 40,41,51,52 Of note, A376S has been associated with failure to NNRTI, particularly nevirapine-containing regimens, 53,54 suggesting a functional link between this mutation and K103N.…”
Section: Novel Hiv-1 Rt C-terminal Mutationsmentioning
confidence: 99%
“…34 The N348I mutation occurred in 11% of viruses in Southern Brazil and it is associated with major resistance to nevirapine, etravirine, and rilpivirine, and as an accessory mutation for thymidine analogs. 40,41,51,52 Of note, A376S has been associated with failure to NNRTI, particularly nevirapine-containing regimens, 53,54 suggesting a functional link between this mutation and K103N.…”
Section: Novel Hiv-1 Rt C-terminal Mutationsmentioning
confidence: 99%
“…In vitro selection experiments and drug susceptibility assays have revealed that the major mutations associated with DPV resistance or cross-resistance are V90I, L100I, K103N, V106I, E138K, Y181C, and Y188L (7,8). Mutations outside the polymerase domain of reverse transcriptase in the connection and/or RNase H domains of reverse transcriptase, including G335D, N348I, T369I, A371V, and A376S, have been shown to cause cross-resistance to NNRTIs (9)(10)(11)(12)(13). Such mutations are missed by most standard population-based genotyping tests and require full-length sequencing of reverse transcriptase.…”
mentioning
confidence: 99%
“…Paredes et al reported that preexisting A376S was associated with an increased risk of virologic failure to NVP (relative hazard (RH) = 10.4; 95 % confidence interval (CI), 2.0-54.7), but did not affect EFV outcome the same way (RH = 0.5; 95 % CI, 0.1-2.2) (p = 0.013) (Paredes et al 2011). A376S confers selective low-level NVP resistance in vitro (Paredes et al 2011).…”
Section: A376smentioning
confidence: 99%
“…A376S confers selective low-level NVP resistance in vitro (Paredes et al 2011). Interestingly, Gupta et al reported that virologic responses to an ETV-containing regimen were slightly diminished when A376S was present (Gupta et al 2011).…”
Section: A376smentioning
confidence: 99%